2010
DOI: 10.1016/j.cbpa.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Residue-specific incorporation of non-canonical amino acids into proteins: recent developments and applications

Abstract: Residue-specific incorporation of non-canonical amino acids into proteins allows facile alteration and enhancement of protein properties. In this review we describe recent technical developments and applications of residue-specific incorporation to problems ranging from elucidation of biochemical mechanisms to engineering of protein-based biomaterials. We hope to inform the reader of the ease and broad utility of residue-specific non-canonical amino acid incorporation with the goal of inspiring investigators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
251
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(259 citation statements)
references
References 48 publications
0
251
0
2
Order By: Relevance
“…22 With the need for more diverse and powerful reporter properties, research groups began to take the Techniques based on exploiting an organism's ribosomal machinery can be applied in theory to any protein, and can be particularly important when the target is a large protein that is not amenable to semisynthesis or difficult to site-selectively label with an exogenous reagent. Three main translation-based methods have become widespread: 1) exploiting promiscuity of wild type synthetases and mutants, 23 2) expression using a chemically acylated tRNA which is then introduced into the expression system containing mRNA encoding a nonsense 3-base or 4-base codon. 24-26 or 3) nonsense expression using an evolved orthogonal tRNA/aminoacyl-tRNA synthetase (AARS) pair recognizing a nonsense (commonly UAG or "amber") codon.…”
Section: Summary Of Approachesmentioning
confidence: 99%
“…22 With the need for more diverse and powerful reporter properties, research groups began to take the Techniques based on exploiting an organism's ribosomal machinery can be applied in theory to any protein, and can be particularly important when the target is a large protein that is not amenable to semisynthesis or difficult to site-selectively label with an exogenous reagent. Three main translation-based methods have become widespread: 1) exploiting promiscuity of wild type synthetases and mutants, 23 2) expression using a chemically acylated tRNA which is then introduced into the expression system containing mRNA encoding a nonsense 3-base or 4-base codon. 24-26 or 3) nonsense expression using an evolved orthogonal tRNA/aminoacyl-tRNA synthetase (AARS) pair recognizing a nonsense (commonly UAG or "amber") codon.…”
Section: Summary Of Approachesmentioning
confidence: 99%
“…Moreover, some functional groups can only be introduced by the use of unnatural amino acids, which in general significantly lower the production yields. 13 The use of chemoselective reactions to selectively modify specific residues in ELPs post-synthesis has been shown to be a promising means to introduce new functionalities and impart new properties to ELPs, especially at their chain ends, 14,15,16,17 and more scarcely at ELP side-chain residues. 18,19 In a previous study, we reported the chemoselective alkylation of all methionine (Met) residues in the ELP sequence (VPGMG) 20 , which contains Met residues in every repeat, and used this modification to tune the LCST of the resulting polysulfonium ELP derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Numerous strategies, including biological 8 and chemical synthesis, 1,2 have been developed to either react with or modify natural residues, or replace them entirely, using highly selective processes. Many of these methods have focused on reaction at or replacement of L-cysteine (Cys), 9 L-methionine (Met), 8,10,11 and N-terminal residues 12,13 since these are often present in low abundance and thus can provide unique sites for functional modification. Most chemical strategies have focused on reactions at highly nucleophilic Cys thiol groups, where a variety of different types of modification are possible.…”
Section: Introductionmentioning
confidence: 99%